2020
DOI: 10.3390/ijms21186519
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte-Rich Platelet-Rich Plasma Enhances Fibroblast and Extracellular Matrix Activity: Implications in Wound Healing

Abstract: Background: Platelet-rich plasma (PRP) is an autologous blood product that contains a high concentration of platelets and leucocytes, which are fundamental fibroblast proliferation agents. L iterature has emerged that offers contradictory findings about leucocytes within PRP. Herein, we elucidated the effects of highly concentrated leucocytes and platelets on human fibroblasts. Methods: Leucocyte-rich, PRP (LR-PRP) and leucocyte-poor, platelet-poor plasma (LP-PPP) were compared to identify their effects on hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 99 publications
1
25
0
Order By: Relevance
“…L-PRP has a 6-fold platelet concentration and increases PDGF-AB and TGF-β1 concentrations compared with whole blood, and also strongly activates the NF-κB pathway and contains a high amount of leukocytes, TNF-α and IL-1β [ 57 ]. The secretion of these factors correlates with the hypothesis of some authors, who consider that L-PRP contributes to inflammation and premature apoptosis [ 58 ]. Furthermore, one study argued that L-PRP may intensify the over-expression of MMP and consequently activate extracellular matrix (ECM) catabolic pathways and excessive inflammation [ 59 ].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…L-PRP has a 6-fold platelet concentration and increases PDGF-AB and TGF-β1 concentrations compared with whole blood, and also strongly activates the NF-κB pathway and contains a high amount of leukocytes, TNF-α and IL-1β [ 57 ]. The secretion of these factors correlates with the hypothesis of some authors, who consider that L-PRP contributes to inflammation and premature apoptosis [ 58 ]. Furthermore, one study argued that L-PRP may intensify the over-expression of MMP and consequently activate extracellular matrix (ECM) catabolic pathways and excessive inflammation [ 59 ].…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, one study argued that L-PRP may intensify the over-expression of MMP and consequently activate extracellular matrix (ECM) catabolic pathways and excessive inflammation [ 59 ]. This concept was also accentuated in another study [ 60 ], which reported that leukocytes in PRP initiate a greater activation of the nuclear factor kappa-light-chain-enhancer of the activated B cells pathway, subsequently resulting in significantly less fibroblast proliferation and a higher concentration of pro-inflammatory cytokines [ 58 , 59 , 60 ]. However, the PRP of these studies contained a high concentration of RBCs and therefore could be the source of this reaction and bias [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WBC levels in L-PRP are more than 100% levels in WB. 9 In Kenmochi's study, almost the same results were obtained, namely that the PLT concentration increased by 4.8 and WBC increased by 2.6 times in L-PRP. 10 In this study, the results obtained were that the group of research subjects who received P-PRP injection showed that the mean RUSS score was significantly higher than placebo in the 6 week post-injury period (p value =0.012, CI 95% =0.25-1.91).…”
Section: Discussionmentioning
confidence: 61%